Workshop on Remote Laboratories: Sharing Expertise, Sharing Resources - Murray, S.; Lowe, D.; Lindsay, Euan; Liu, D. (Australasian Association for Engineering Education, 2007)
Laboratories are an integral element of Engineering courses within Australia. The Engineers Australia accreditation criteria includes "proficiency in appropriate laboratory procedures; the use of test rigs, instrumentation and test equipment;" as well as "Access to simulation, visualisation, analysis, design, documentation, planning, communication and management tools as well as test and measurement equipment and information resources appropriate to current industry practice". Laboratory infrastructure is, however, expensive to maintain and imposes significant logistical constraints on course delivery. One option to reduce these burdens is the use of remote laboratories where students are able to remotely interact with the laboratory hardware. Remote laboratories are an increasingly popular innovation in engineering education, but their development has for the large part been an ad hoc process - they are developed in isolation to address the needs of a particular laboratory class; and they are often regarded as a "second-best" substitute for the real thing. This workshop is aimed at sharing experiences within the Australian Engineering education environment, with the goal of ultimately developing a remote laboratories special interest group and/or consortium tasked with the ongoing development and sharing of remote laboratory facilities.